Determinants of City Growth in Brazil - da Mata, Daniel; Deichmann, Uwe; Henderson, J. Vernon; Lall, Somik V.; Wang, Hyoung Gun (World Bank, Washington, DC, 2012)
The authors examine the determinants of Brazilian city growth between 1970 and 2000. They consider a model of a city that combines aspects of standard urban economics and the new economic geography literatures. For the empirical analysis, the authors construct a dataset of 123 Brazilian agglomerations and estimate aspects of the demand and supply side, as well as a reduced form specification that describes city sizes and their growth. Their main findings are that increases in rural population supply, improvements in interregional transport connectivity, and education attainment of the labor force have strong impacts on city growth. They also find that local crime and violence, measured by homicide rates, impinge on growth. In contrast, a higher share of private sector industrial capital in the local economy stimulates growth. Using the residuals from the growth estimation, the authors also find that cities that better administer local land use and zoning laws have higher growth. Finally, their policy simulations show that diverting transport investments from large cities toward secondary cities does not provide significant gains in terms of national urban performance.